Kinetika Perubahan Sifat Fisik dan Kadar Tanin Biji Sorgum (Sorghum Bicolor L.) Selama Perendaman - Asropi Asropi; Nursigit Bintoro; Joko Nugroho Wahyu Karyadi; Sri Rahayoe; Arifin Dwi Saputro (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2019)
Some studies have been done to examine that the soaking process of sorghum seeds decrease the tannin level, but have not yet examined the kinetics of reaction changes during soaking. The aim of this experiment was to study the kinetics of changes on physical characteristics and tannin level of sorghum seeds during soaking. This experiment used milled and not milled red sorghum seeds which were soaked for 24 hours in distilled and alkaline solution at 30, 45, and 60 ºC. Observed parameters included water content, tannin content, and hardness, which were analyzed using statistical data and the kinetics of parameter change rate. Temperature treatment had a significant effect on the changes in all parameters of sorghum seeds during soaking. The increase in temperature accelerated the diffusion coefficient (Deff) in a range between 6.6345x10-12 m2/second to 13.5519x10-12 m2/second and energy activation of 8.054 kJ/mol; 3.274 kJ/mol; 3.183 kJ/mol; and 7.29 kJ/mol on the distilled water soaking treatment of not milled sorghum seeds, alkaline soaking treatment of not milled seeds, the distilled water soaking treatment of milled sorghum seeds, and alkaline soaking treatment of milled seeds. The highest decrease in tannin content was 77.9%, that was obtained in the treatment of alkaline soaking treatment of milled seeds at 60 ºC. The highest increase in volume occurred in the treatment of alkaline soaking treatment of milled seeds (76.0%). The value of the constant rate tended to increase with the increasing temperature of the soaking process. This means that the changes in the parameter were faster at a higher temperature, so the energy activation used is lower.